Depressão e trabalho: relações segundo o imaginário coletivo de um grupo de comerciários - Fernandes, Andréa Aparecida (2020)
The present dissertation is found by two studies that complement each other. Study 1 appears as a review of the literature on the use of the concept of collective imagery in its psychoanalytical sense. Thus, Study 1, theoretical-methodological contextualization to Study 2, which empirically explored a specific facet of depression in the workplace. Study 1 aimed to establish a panorama of the national scientific production conveyed in the format of empirical articles and devoted to the psychoanalytic exploration of the collective imagination. The analysis corpus was composed of 23 references, selected from searches carried out with databases. It was found that a national scientific production dedicated to the subject offers, in different audiences, the demarcation of the non-conscious core of group subjectivities with respect to a variety of phenomena, as well as showing that the collective imagination, as psychoanalytically elaborated, is not limited a set of exclusively intrapsychic contents, but, yes, it encompasses several human manifestations connected to intersubjective regions that are built from everyday interactions. It was also found that, in general, as selected references can be selected from a methodological point of view. Study 2 aimed to understand how relationships exist between depression and work according to the collective imagination of a group of businessmen. The participants were nine shopkeepers who worked in two stores in the same furniture and appliance chain. The instrument used was a group interview guided by the Procedure of Drawings-Stories with Theme (PDE-T). The analysis corpus was subjected to fluctuating readings, directed to the information of interpretations about the non-conscious senses that structure the participants' collective imagery about depression. In summary, it was found that, according to the participants, the affect severely affects functionality, including in the context of work. However, the work environment was not emphasized as a trigger for the fr options that, for most of them, would trigger depression. And the feeling of loneliness, pointed out as both a cause and a consequence of depression, was limited to personal life. Soon, it became possible to identify some (im) possible relationships between depression and work according to the collective imagination of a group of businessmen.